2000
DOI: 10.1161/01.str.31.1.9
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Transient Ischemic Attack Incidence in Novosibirsk, Russia, 1987–1988 and 1996–1997

Abstract: Background and Purpose-Population-based data on transient ischemic attack (TIA) incidence are scarce. This study defines incidence rates of first-ever TIA in Novosibirsk, Russia, during 1987Russia, during -1997 and compares the incidence of first TIA with that of first stroke. Methods-This is a prospective registry population-based study of all new cases of TIA and stroke in an overall population of 455 765 residents of Novosibirsk. All new TIA and stroke incident cases (whether inpatient or outpatient) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…These findings have been reported in previous studies. 18,25,26 Early stroke risk was quite similar to that previously reported. 3,4 We detected a high proportion of TIA patients who have not been admitted to hospital (50%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings have been reported in previous studies. 18,25,26 Early stroke risk was quite similar to that previously reported. 3,4 We detected a high proportion of TIA patients who have not been admitted to hospital (50%).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison with others population-based studies 11,12,18,22,[25][26][27][28] (Table 4), the incidence rate in Udine, age-adjusted to the European standard population (0.25), was very similar to that in Segovia (0.21), Dijon (0.27), and Novosibirsk (0.31). [25][26][27] Instead, the rates found in Belluno (0.58) and Rochester (0.65) were Ͼ2-times higher. 12,22 We think that our findings are plausible for the following reasons.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This was higher than that found in the Oxford Vascular Study (OXVASC) study, where the annual TIA incidence was 58 (95% CI, 46-69) per 100 000 people, 15 but in the middle of the range when compared with other populations studied since 2000 (Figure). [1][2][3][4]6,[16][17][18][19][20] This likely reflects higher stroke incidence in our population compared with other developed countries. 21 Ethnic differences were seen with Asian/Other having half the incidence of TIA compared with the other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…A study (in Rochester, Minnesota) observed a crude age-and sex-adjusted incidence rate of 68 per 100,000 persons per year for the years 1985 to 1989, the highest incidence of 584 per 100,000 noted among individuals aged 75 to 84 [8]. Other population-based TIA incidence rates range from 18 per 100,000 persons per year from 1987 to 1988 in Novosibirsk, Russia [9] to 37 per 100,000 persons per year from 1970-1973 in Estonia [10]. Data from Sweden, England, France, and Japan have also been within this range [11][12][13][14].…”
Section: Prevalence and Incidencementioning
confidence: 99%